(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This research paper explores the transformative potential of blockchain technology and machine learning (ML) in the realm of education enterprise technologies. As the educational landscape continues to evolve in the digital age, these cutting-edge technologies offer innovative solutions to longstanding challenges in areas such as credential verification, personalized learning, and administrative efficiency. This study examines the current applications of blockchain and ML in education, analyzes their benefits and limitations, and forecasts their future impact on the industry. By synthesizing recent research and case studies, this paper aims to provide a comprehensive understanding of how these technologies are reshaping education enterprise technologies and paving the way for more efficient, secure, and personalized learning experiences.